plant community data - Robroek, Bjorn J. M.; Jassey, Vincent E. J.; Payne, Richard J.; Martí, Magalí; Bragazza, Luca; Bleeker, Albert; Buttler, Alexandre; Caporn, Simon J. M.; Dise, Nancy B.; Kattge, Jens; Zając, Katarzyna; Svensson, Bo H.; et al. (Dryad Digital Repository, 2017)
Abundance data (% cover) for all vascular plant and bryophyte species from five randomly chosen hummocks and lawns (0.25 m2 quadrats; ten in total) across 56 European Sphagnum-dominated peatlands were collected in two consecutive summers (2010 and 2011). Vascular plants and Sphagnum mosses were identified to the species level. Non-Sphagnum bryophytes were identified to the family level. Lichens were recorded as one group.